A review of fundamental principles and applications of polymer nanocomposites filled with both nanoclay and nano-sized carbon allotropes – Graphene and carbon nanotubes. (April 2020) - Kausar, Ayesha
Advancements in polymer/nanoclay nanocomposites have supported the development of distinctive preparation strategies and characteristic features. High-performance polymer/nanoclay nanocomposites have applications in aerospace, automotive, construction, environmental, and biomedicine. To further improve polymer/nanoclay nanocomposite performance, nanoclay nanobifillers have been considered. In this regard, nano-sized carbon allotropes are potential contenders to form nanoclay nanobifillers. This article presents a detailed and state-of-the-art review on polymer/nanoclay nanobifiller nanocomposites. The primary focus of this pioneering effort is to deliver an up-to-date overview on polymer/nanoclay nanobifiller nanocomposites along with their categorization, fabrication, properties, and uses. Nanoclay nanobifiller designs using carbon nanotube, graphene, and fullerene are considered. Consequently, ensuing nanocomposite categories are discussed including polymer/nanoclay-carbon nanotube, polymer/nanoclay-graphene, and polymer/nanoclay-fullerene nanocomposites. The dispersion properties and alignment of nanoclay nanobifiller in polymeric nanocomposites have been investigated. Enhancing the interfacial bonding strength between matrix and nanoclay nanobifiller enhances the resulting nanocomposite physical properties. Application areas for polymer/nanoclay nanobifiller nanocomposites include supercapacitors, non-flammable materials, and self-healing materials. The discussion also highlights potential future directions for this emerging research field. Forthcoming advancements in polymer/nanoclay nanobifiller nanocomposites must focus the intensive design control, nanobifiller functionality, new processing techniques, superior dispersion, and enhanced features to further broaden the application prospects of these materials.